Ionic and conformational mobility in poly(vinylidene fluoride)/ionic liquid blends: dielectric and electrical conductivity behavior - Correia, Daniela Maria Silva (2018)
The glass transition dynamics and the charge transport for blends composed of poly(vinylidene fluoride) (PVDF) and the ionic liquid (IL) 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide, [Emim] [TESI] have been investigated as a function of different IL content (0, 10, 25 and 40 % wt) by differential scanning calorimetry (DSC), dynamic-mechanical analysis (DMA) and broadband dielectric relaxation spectroscopy (BDS) in wide frequency and temperature ranges (0.1 Hz-1 MHz and -120 to 150 degrees C, respectively). The inclusion of the IL in the polymer matrix affected the main relaxation process (beta-relaxation) of the amorphous phase of the polymer matrix detected with all the techniques employed. It is demonstrated, that the chain segments of PVDF and the IL are mixed at the nanometer range. The blends were homogeneous regardless of the amount of IL and the glass transition temperature (Tg) shifted to lower temperatures as the IL content was increased. A good agreement between the Tg measured by BDS and DSC was observed for all PVDF/IL samples. The conductivity formalism revealed significant contributions of the IL concentration to the conductivity behavior of the blends in that is described by charge motion and electrode polarization effects. The activation energy of all the PVDF/IL samples, calculated by Dyre model, decreased with IL addition with respect to that of neat PVDF.